Pedagogical competency development of prospective special education teachers through based learning models project - Imam Yuwono; Dewi Ratih Rapisa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Learning in elementary schools is presented thematically by combining several subjects in a theme. In special schools and inclusive schools, teachers with special education backgrounds have an important role in simplifying the subject matter by adjusting the results of each child's assessment, one of which is science material. Support for learning services for special needs children requires various preparations from various parties such as educators so that skills in preparing materials, determining approaches, models, methods, and learning media become a pedagogical competency that must be mastered by prospective special education teacher students. This study aims to describe the implementation of the Project Based Learning model which consists of stages of planning, implementation, evaluation and presentation to build the pedagogical competence of students of the Special Education Study Program as prospective teachers in teaching science material to Children with Special Needs. This research was conducted using a qualitative approach with the type of case study. The results showed that lectures with project-based learning models through the stages of planning, implementation, presentation and evaluation were able to build student pedagogical competence in terms of special needs children's assessment, learning assessment, lesson plans modification, making science learning media, role-playing lesson plans modification, and implementing lesson plans that has been prepared in order to prepare special education students to become professional teacher candidates.